"Being on the Positive End of Every Negative Statistic": Expanding Inclusion of Gifted Education Through Considerations of Critical Consciousness as Double Giftedness. (June 2022) - Bryson, Brandy S.
The narrow manner in which giftedness is often regarded perpetuates the underrepresentation of students of Color in gifted education programs, particularly for Black students. This case study highlights the story of a gifted Black high school student attending a predominantly White high school in the South. Bianca's story illuminates her struggle with myriad racialized challenges within and outside of school and, more importantly, demonstrates her sophisticated and critically conscious appraisal of structural inequities. Interpreted through the lens of critical consciousness, Bianca's story of giftedness illuminates her complex understandings of societal and institutional workings. Given the complexity and effort required to participate in critical ways of knowing, especially concerning the ways in which race and racism function, this study highlights that critically conscious students like Bianca are, in fact, doubly gifted and can offer insights to expand commonly held notions of giftedness and greater inclusivity in gifted education. Implications for educators and policy makers are discussed.